Iron-deficiency Anemia in Children with Febrile Seizure: A Case-Control Study - GHASEMI, Fateme; VALIZADEH*, Fateme; TAEE, Nadere (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Ghasemi F, Valizadeh F, Taee N. Iron-deficiency Anemia in Children with Febrile Seizure: A Case-Control Study. Iran J Child Neurol. 2014 Spring 8(2):38-44. Objective Considering the recurrence of febrile seizure and costs for families, many studies have attempted to identify its risk factors. Some recent studies have reported that anemia is more common in children with febrile convulsion, whereas others have reported that iron deficiency raises the seizure threshold. This study was done to compare iron-deficiency anemia in children with first FS with children having febrile illness alone and with healthy children. Materials & Methods This case-control study evaluated 300 children in three groups (first FS, febrile without convulsion, and healthy) in Khoramabad Madani Hospital from September 2009 to September 2010. Body temperature on admission was measured using the tympanic method. CBC diff, MCV, MCH, MCHC, serum iron, plasma ferritin and TIBC tests were performed for all participants. Data were analyzed by frequency, mean, standard deviation, ANOVA, and chi-square statistical tests. Odds ratios were estimated by logistic regression at a confidence level of 95%. Results Forty percent of the cases with FS had iron-deficiency anemia, compared to 26% of children with febrile illness without seizure and 12% of healthy children. The Odds ratio for iron-deficiency anemia in the patients with FS was 1.89 (95% CI, 1.04-5.17) compared to the febrile children without convulsion and 2.21 (95% CI, 1.54-3.46) compared to the healthy group. Conclusion Children with FS are more likely to be iron-deficient than those with febrile illness alone and healthy children. Thus, iron-deficiency anemia could be a risk factor for FS. References 1. Østergaard J R. Febrile Seizures. Acta Pædiatr 2009;98(5):771-3. 2. Jones T, Jacobsen SJ. Childhood Febrile Seizures: Overview and Implications. Int J Med Sci. 2007; 4(2):110-4. 3. Flury T, Aebi C, Donati F. Febrile Seizures and Parental Anxiety: Does Information Help? Swiss Med Wkly 2001;131:556–60. 4. Kliegman RM, Stanton BF, St Geme JW, Schor NF, Behrman RE. Nelson Textbook of Pediatrics. 19th ed. Philadelphia (PA): WB Saunders Company; 2011. p.2017. 5. Pisacane A, Sansone R, Impagliazzo N, Coppola A, Rolando P, D’Apuzzo A, et al. Iron Deficiency Anemia and Febrile Convulsions: Case-control Study in Children under 2 Years. BMJ 1996;313 (7053):343. 6. Lozoff B, Beard J, Connor J, Barbara F, Georgieff M, Schallert T, et al. Long-lasting Neural and Behavioral Effects of Iron Deficiency in Infancy. Nutr Rev 2006;64(5 Pt 2):34–43. 7. Parks YA, Wharton BA. Iron Deficiency and the Brain. Acta Paediatr Scand 1989;361:(Suppl 1):71–7. 8. Ur-Rehman N, Billoo AG. Association between Iron Deficiency Anemia and Febrile Seizures. J Coll Physicians Surg Pak 2005;15(6):338-40. 9. Daoud AS, Batieha A, Abu-Ekteish F, Gharaibeh N, Ajlouni S, Hijazi S. Iron Status: A Possible Risk Factor for the First Febrile Seizure. Epilepsia 2002;43(7):740-3. 10. Hartfield DS, Tan J, Yager JY, Rosychuk RJ, Spady D, Haines C, et al. The Association between Iron Deficiency and Febrile Seizures in Childhood. Clin Pediatr (Phila) 2009;48(4):420-6. 11. Momen A, Nikfar R, Karimi B. Evaluation of Iron Status in 9-month to 5-year-old Children with Febrile Seizures: A Case-control Study in the South West of Iran. Iran J Child Neurol 2010;4(2):45-50. 12. Talebian A, Momtazmanesh N. Febrile Seizures and Anemia. Iran J Child Neurol 2007;31-3. 13. Kobrinsky NL, Yager JY, Cheang MS, Yatscoff RW, Tenenbein M. Does Iron Deficiency Raise the Seizure Threshold? J Child Neurol 1995;10(2):105–9. 14. Salehi Omran MR, Tamaddoni A, Nasehi MM, Babazadeh H, Alizadeh Navaei R. Iron Status in Febrile Seizure: A Case-control Study. Iran J Child Neurol 2009:3(3):40-3. 15. Amirsalari S, Keihanidost Z, Ahmadi M, Sabouri A, Kavemanesh Z, Afshar P, et al. Relationship between Iron Deficiency Anemia and Febrile Seizures. Iran J Child Neurol 2010;14(1):27-30. 16. Bidabadi E, Mashouf M. Association between Iron Deficiency Anemia and First Febrile Convulsion: A Case–control Study. Seizure 2009;18:347-51. 17. Oski FA, Brugnara C, Nathan DG. A Diagnostic Approach to the Anemic Patients. In: Nathan DG, Orkin SH, editors. Nathan and Oski’s Hematology of Infancy and Childhood. 7th ed. Philadelphia: WB Saunders Company; 2008. Appendix 11. 18. Vaswani RK, Dharaskar PG, Kulkarni S, Ghosh K. Iron Deficiency as a Risk Factor for First Febrile Seizure. Indian Pediatr 2009;47(5):437-9. 19. Sadeghzadeh M, Khoshnevis P, Mahboubi E. Iron Status and Febrile Seizure- A Case Control Study in Children Less Than 3 Years. Iran J Child Neurol 2012;6(4):27-31. 20. Idro R, Gwer S, Williams TN, Otieno T, Uyoga S, Fegan G, et al. Iron Deficiency and Acute Seizures: Results from Children Living in Rural Kenya and a Metaanalysis. PLoS One 2010;5(11):e14001. 21. Auvichayapat P, Auvichayapat N, Jedsrisuparp A, Thinkhamrop B, Sriroj S, Piyakulmala T, et al. Incidence of Febrile Seizures in Thalassemic Patients. J Med Assoc Thai 2004:87(8):970-3.